Design of Information Systems in Web-Based Medicine Ordering and Procurement - Vaira, Tischa; Rohmah, Alfiyatu; Zaeniyah, Siti; Pribadi, Prasojo; Santoso, Setiyo Budi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The drug distribution process determines the sustainability of drug stocks in pharmaceutical services. It is hoped that the design of an information system for drug procurement and ordering can make the distribution process more effective and efficient. While information systems for drug procurement and ordering exist, they are typically designed for individual distributors. This research aims to design an information system by displaying flowcharts that map the drug procurement and ordering process, and by developing user interfaces that facilitate interaction with the system. The research was carried out through a Literature Review. Reference searches were conducted using the Google Scholar search engine. The keywords used in the keyword search were